Orientasi Desain Pembelajaran PAI dan Budi Pekerti pada Kurikulum Merdeka - Yasmin RF, Firyal (Perkumpulan Peneliti dan Pegiat Literasi, 2024)
This study aims to analyze the design of Islamic Religious Education (PAI) and Ethics learning and its supporting programs at SMAN 01 Garut, within the framework of the Independent Curriculum implementation. The research approach used is descriptive analysis, with data collection techniques through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman method. The main findings show that PAI and Ethics teachers actively participate in the preparation of various important documents such as syllabi, educational calendars, annual programs, and semester programs, involving all school elements, including committees and parent representatives. This involvement aims to enhance the quality of learning through close collaboration among related parties. This research makes a significant contribution to the literature on the implementation of the Independent Curriculum in senior high schools, particularly in the context of religious and ethical education. However, this study has limitations in terms of the number of respondents and the limited duration of the research. The prospects for developing the results of this study include increasing the use of technology in learning and applying broader collaborative strategies in various school contexts. Further implications indicate the need for ongoing teacher training to optimize the quality of learning and adapt the curriculum to local needs.